Manuscript belongs to the Forum Reusing sludge from surface water treatment plant for hexavalent chromium adsorption in aqueous solution - Duc, Nguyen Duc Dat; Thanh, Le Minh; Phong, Nguyen Tan (Vietnam Journal of Science and Technology, 2022)
Contaminants in plating wastewater are hard to remove, especially hexavalent chromium ions. This waste stream contains a large amount of Cr6+, a highly toxic metal, potential to cause cancer. To reduce this pollution, sludge from a supply water treatment plant (DWTS) has been used to make adsorbent. This sludge was denaturized by thermal method. After that, a plating synthetic waste stream contained Cr6+ was treated by a batch adsorption model with adsorbent made from DWTS. pH, amount of adsorbent, and treatment time were investigated to determine the suitable treatment conditions. The study was also evaluated the suitability of two adsorption models Langmuir and Freundlich. Results showed that, under the conditions of pH = 6.0, the adsorbent content of 25.0 g/l, after 90.0 minutes, Cr6+ content remained 0.14 mg/l, close to QCVN 40:2011/BTNMT, column B. The parameters of the Langmuir and Freundlich adsorption equations are: qmax = 12.578 mg/g; Kads = 0.747 l/mg; n = 0.338; kf = 5.138. The Freundlich isothermal model is better fitted to the chromium adsorption process than Langmuir isothermal model.